Gambaran Aktivitas Fisik Pada Mahasiswa Sebelum Dan Saat Sfh (Study From Home) Di Masa Pandemi Covid-19 - Vera Kasmira; Aqila Permata Dewi; Adhila Fayasari (Jurnal Gizi dan Kuliner, 2021)
Decreased physical activity can affect individual’s health and have an impact on increasing the risk of non-communicable diseases such as obesity, hypertension, and diabetes mellitus. The Covid-19 pandemic has caused the Government to implement a study from home (SFH) policy to suppress the spread of the Covid-19 virus. This affects the physical activities carried out by students. This study aims to describe the level of physical activity and exercise in students before SFH and during SFH during the pandemic. The research methodology used is a quantitative study using an online survey. The research subjects consisted of 73 students of Binawan University semester 1-8. Giving the category of physical activity is done by calculating the average Physical Activity Level (PAL) in 1 day for a week. The results showed that 55 students (75.3%) were classified as light physical activity during SFH, from before SFH only 34 students (46.6%), moderate activity 19.2% from 45.2% and heavy activity only 5, 5% from the previous 8.2%. Only 25 students (34.2%) did sports activities 1-2 times per week during SFH compared to 53 students (72.6%). This study concluded that there was a decrease in physical activity and exercise habits in students during SFH during the pandemic. This is influenced by the implementation of learning from home and restrictions on activities outside the home and public facilities. Keywords: Physical activity; Students; Physical Activity Level (PAL); Study from Home